The Relationship Between Emotional Intelligence And Academic Achievement Among Fourth-Grade Elementary School Students - Fitriayani Fitriayani; Ahmad Ahmad; Waode Ekadayanti (CV. Gerasi Insan Nusantara, 2025)
Emotional intelligence is an important internal factor that supports students' learning success by enabling them to recognize and regulate emotions, maintain self-motivation, and establish positive social relationships during the learning process. This study aimed to examine the relationship between emotional intelligence and academic achievement among fourth-grade students at SD Negeri 2 Konda, South Konawe Regency. A quantitative approach with a correlational research design was employed. The population and sample consisted of all 32 fourth-grade students, selected using a total sampling technique. Data on emotional intelligence were collected using a questionnaire, while academic achievement data were obtained from students' first-semester report-card grades. The data were analyzed using descriptive statistics and Pearson's Product-Moment correlation with the assistance of IBM SPSS. The results showed that the students' emotional intelligence and academic achievement were generally in the good category. Pearson's correlation analysis produced a correlation coefficient of r = 0.764 with a significance value of p < 0.001, indicating a strong, positive, and statistically significant relationship between emotional intelligence and academic achievement. The coefficient of determination (R²) was 0.583, indicating that emotional intelligence contributed 58.3% to the variation in students' academic achievement, while the remaining 41.7% was associated with other factors not examined in this study. Thus, higher emotional intelligence was associated with higher academic achievement among fourth-grade students at SD Negeri 2 Konda.